Two photon absorption in TeO2-ZnO glass at different laser irradiances. Issue 1 (17th February 2015) - Thomas, Rose Leena; Hari, Misha; Nampoori, V P N; Radhakrishnan, P; Thomas, Sheenu
Abstract: TeO2 -ZnO glasses were prepared and their optical properties were determined. In the present work we measured the optical non-linearity of the glass using a single beam z-scan technique given by Sheike Bahe et al. The open aperture z-scan curve of TeO2 -ZnO proves that nonlinear optical properties are highly fluence dependent.